A randomized controlled trial of patient recall after detailed written consent versus standard verbal consent in adults with routine orthopaedic trauma - Amjad M. Aslam; James Kennedy; Haider Seghol; Nikhil Khisty; Thomas A. Nicols; Sam Adie (Bone & Joint Open, 2023)
Aims: Patient decision aids have previously demonstrated an improvement in the quality of the informed consent process. This study assessed the effectiveness of detailed written patient information, compared to standard verbal consent, in improving postoperative recall in adult orthopaedic trauma patients. Methods: This randomized controlled feasibility trial was conducted at two teaching hospitals within the South Eastern Sydney Local Health District. Adult patients (age ≥ 18 years) pending orthopaedic trauma surgery between March 2021 and September 2021 were recruited and randomized to detailed or standard methods of informed consent using a random sequence concealed in sealed, opaque envelopes. The detailed group received procedure-specific written information in addition to the standard verbal consent. The primary outcome was total recall, using a seven-point interview-administered recall questionnaire at 72 hours postoperatively. Points were awarded if the participant correctly recalled details of potential complications (maximum three points), implants used (maximum three points), and postoperative instructions (maximum one point). Secondary outcomes included the anxiety subscale of the Hospital and Anxiety Depression Scale (HADS-A) and visual analogue scale (VAS) for pain collected at 24 hours preoperatively and 72 hours postoperatively. Additionally, the Patient Satisfaction Questionnaire Short Form (PSQ-18) measured satisfaction at 72 hours postoperatively. Results: A total of 60 patients were randomized, 32 to the standard group and 28 to the detailed group. Patients in the detailed group had significantly higher total recall score compared to the standard group (mean difference 1.29 points (95% confidence interval (CI) 0.51 to 2.08); p = 0.002). There were no differences in HADS-A (mean difference 0.39 (95% CI -2.11 to 2.88); p = 0.757), VAS pain (mean difference 5.71 (95% CI -22.25 to 11.11); p = 0.499), or PSQ-18 (mean difference 0.499; 95% CI -1.6 to 3.42; p = 0.392). Conclusion: Detailed written tools are useful in improving postoperative recall in adult orthopaedic trauma patients. Cite this article: Bone Jt Open 2023;4(2):104–109.